Multilevel analysis of self-perception in oral health and associated factors in Southern Brazilian adults: a cross-sectional study - Marilisa Carneiro Leão Gabardo; Samuel Jorge Moysés; Simone Tetu Moysés; Marcia Olandoski; Maria Teresa Anselmo Olinto; Marcos Pascoal Pattussi (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
The aim of this study was to evaluate the association between individual and contextual variables related to self-perception in oral health among residents in the municipality of São Leopoldo, Rio Grande do Sul State, Brazil. The cross-sectional design involved 1,100 adults in 38 census tracts. The self-perception was evaluated using the Oral Health Impact Profile (OHIP-14) tool. A logistic multilevel analysis was performed. The multivariate analysis revealed that those who are of the female gender, older, with lower scores of quality of life and less social support, with poor healthy eating habits, smokers and those living in low-income census tracts presented higher odds of reporting worse oral health self-perception (OHIP-1). We concluded that individual and contextual variables are associated with oral health self-perception. This is essential information for planning health services wishing to meet the health needs of the population.